Peningkatan Kompetensi Guru dalam Menulis Proposal Penelitian Tindakan Kelas melalui Pelatihan dengan Model Pembelajaran Andragogi - Rohmat Santosa (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Classroom action research (PTK) training really needs to be carried out so that teachers are motivated to do scientific publications. The andragorial learning model is considered more appropriate for adults than the lecture method. The purpose of this study was to find out the process of training in writing PTK proposals using the andragogical learning model for 11 teachers at SMK Negeri 1 Sedayu in 2022 in order to increase teacher competence in writing CAR proposals. The PTS model used is the Kemmis and McTaggart models with the stages of planning, implementing, observing and reflecting. Based on the planning / pre-cycle stage, the percentage of teachers' promotion at SMK N 1 Sedayu was very low (20%) due to a lack of publication value. In cycle 1, only 2 components, the research title and problem formulation, received good marks, the other components received fair scores (n=61-72). After cycle 2, overall there was an average increase of ±15% so that each component category turned out to be good (≥80). Based on the results of the research, it can be concluded that the CAR proposal writing training with andragogy learning strategies succeeded in increasing teacher competence in writing proposals. Training on writing CAR proposals using the andragogical learning model is most effective in increasing the ability to identify problems and determine research procedures. The part of the PTK proposal component that still requires more detailed training is data collection techniques.